Adverse drug reactions in special populations – the elderly - Davies, E A (Br J Clin Pharmacol, 2015)
The International Conference on Harmonization considers older people a ‘special population’, as they differ from younger adults in terms of comorbidity, polypharmacy, pharmacokinetics and greater vulnerability to adverse drug reactions (ADRs). Medical practice is often based on single disease guidelines derived from clinical trials that have not included frail older people or those with multiple morbidities. This presents a challenge caring for older people, as drug doses in trials may not be achievable in real world patients and risks of ADRs are underestimated in clinical trial populations. The majority of ADRs in older people are Type A, potentially avoidable and associated with commonly prescribed medications. Several ADRs are particularly associated with major adverse consequences in the elderly and their reduction is therefore a clinical priority. Falls are strongly associated with benzodiazepines, neuroleptics, antidepressants and antihypertensives. There is good evidence for medication review as part of a multifactorial intervention to reduce falls risk in community dwelling elderly. Multiple medications also contribute to delirium, another multifactorial syndrome resulting in excess mortality particularly in frail older people. Clostridium difficile associated with use of broad spectrum antibiotics mainly affects frail older people and results in prolonged hospital stay with substantial morbidity and mortality. Antipsychotics increase the risk of stroke by more than three-fold in patients with dementia. Inappropriate prescribing can be reduced by adherence to prescribing guidelines, suitable monitoring and regular medication review. Given the heterogeneity within the older population, providing individualized care is pivotal to preventing ADRs.